Changes of Landscape Spatial Structure as a Result of Transformation of Land-Ownership (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of the research is to analyse the landscape structure changes from the end of the Soviet times in 1974– 1986 until 2005 when market economy existed in Lithuania. The changes of landscape structure were observed in 100 sample areas (squares) each of them having 2.5 km2 area and distributed in different landscape types. The changes in sample areas (squares) with determination of land cover structure transformations were observed using topographic photos and ortophoto images at a scale 1:10 000. More distinct manifestation of landscape re-naturalisation through land abandonment and conversion to forests, swamps and shrubs, also through transformation of arable land to meadows and pastures was the main direction of land cover changes. The opposite but lower scale conversion of forests, shrubs and other land use types to agrarian fields was also noticed. Acceleration of the conversion of landscape structure towards technogenisation through quick expansion of construction, recreational use and development of infrastructure was another important landscape structure conversion going on in the opposite direction of technogenisation. It manifested mainly as the change of agrarian fields, suburban gardens to built-up territories and as increase of percentage of other land use types related to them (ponds, streets and roads).